PERAN REFLEKSI ETIKA DALAM PEMBENTUKAN INTEGRITAS APARATUR KEPOLISIAN: PENGARUH ETIKA KERJA DAN KOMITMEN ORGANISASI DI POLRES PAREPARE - Imran Nur Alim; Iwan Perwira; Hernita Hernita (Universitas Dharmawangsa, 2026)
This study examines the influence of work ethic and organisational commitment on police integrity, with ethical reflection acting as a mediating variable at the Parepare Police Resort. Using a quantitative explanatory approach, the study involved 249 respondents selected from 660 personnel through the Slovin formula. Data were gathered using Likert-scale questionnaires and analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that work ethic and organisational commitment positively and significantly affect both ethical reflection and integrity. Ethical reflection also significantly influences integrity and partially mediates the relationship between work ethic, organisational commitment, and integrity. These results indicate that police integrity is shaped not only by organisational values and structural factors but also by the internalisation of ethical reflection. The study contributes to public sector human resource management theory and offers practical insights for strengthening ethics and integrity development within police institutions.